Pemetaan Aset Desa oleh Badan Usaha Milik Desa (BUMDes) untuk Pembangunan UMKM Pariwisata - Fauzi Adnan; LV Ratna Devi Sukantalawati; Yuyun Sunesti (Kaganga:Jurnal Pendidikan Sejarah dan Riset Sosial Humaniora, 2025)
This study aims to describe the mapping of village assets by Village-Owned Enterprises (BUMDes) in supporting the development of Micro, Small, and Medium Enterprises (MSMEs) in the tourism sector, especially in Geger Village. This study uses a qualitative approach with a case study method used in this study to gain an in-depth understanding of the process, actor involvement, and obstacles in mapping village assets. The results of the study show that the mapping process was carried out in a participatory manner, involving BUMDes administrators, village government, RT, RW, MSME actors, and village activists. Mapping begins with determining the theme of the discussion as the basis for identifying assets, which are then visualized in the form of a spatial representation of the village area. However, the main obstacle faced is the less than optimal utilization of assets, especially the available natural resources. Most assets such as reservoirs, empty land, fields, and rice fields have not been utilized effectively for tourism activities. Of the six existing reservoirs, only one has been managed for tourism purposes, while the rest have not been utilized. This reflects the still low understanding and capacity of village asset management by stakeholders. This study recommends increasing capacity and cross-sector collaboration to optimize the use of village assets to support the development of sustainable tourism MSMEs. Keywords: Development, Tourism MSMEs, Village Asset Mapping, Village-Owned Enterprises (BUMDes ).